2005
DOI: 10.1210/jc.2004-2159
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Thr130Ile and Val255Met Polymorphisms of the Hepatocyte Nuclear Factor-4α (HNF4A): Gene Associations with Type 2 Diabetes or Altered β-Cell Function among Danes

Abstract: HNF4A encodes an orphan nuclear receptor that plays crucial roles in regulating hepatic gluconeogenesis and insulin secretion. The aim of the present study was to examine two rare missense polymorphisms of HNF4A, Thr130Ile and Val255Met, for altered function and for association with type 2 diabetes (T2D). We have examined these polymorphisms 1) by in vitro transactivation studies and 2) by genotyping the variants in 1409 T2D patients and in 4726 glucose-tolerant Danish white subjects. When tested in COS7 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…In a case-control study with a power of Ͼ80% to detect a relative risk of Ͻ1.2 with the observed allele frequency of 12%, we did not find an association with type 2 diabetes. Also, haplotype studies, including previously examined variants in the genomic region (15,18), did not reveal an association with type 2 diabetes. Genotype-quantitative trait studies in 4,456 subjects with NGT and normoglycemia suggested an association between the polymorphism and a reduced fasting level of serum total cholesterol and serum HDL cholesterol, indicating that these linked polymorphisms may affect the expression of HNF4A in the liver.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In a case-control study with a power of Ͼ80% to detect a relative risk of Ͻ1.2 with the observed allele frequency of 12%, we did not find an association with type 2 diabetes. Also, haplotype studies, including previously examined variants in the genomic region (15,18), did not reveal an association with type 2 diabetes. Genotype-quantitative trait studies in 4,456 subjects with NGT and normoglycemia suggested an association between the polymorphism and a reduced fasting level of serum total cholesterol and serum HDL cholesterol, indicating that these linked polymorphisms may affect the expression of HNF4A in the liver.…”
Section: Discussionmentioning
confidence: 82%
“…Among 4,456 subjects with NGT and normoglycemia, there was a significant association between the polymorphism and alterations in fasting levels of serum total cholesterol and HDL cholesterol (P ϭ 0.02 and 0.02, respectively) ( Table 2). Association studies were also carried out using haplotypes based on single nucleotide polymorphisms identified and investigated in previous studies (15,18). However, there were no extended significant associations with diabetes or any relevant pre-diabetic trait for any combinations, including combinations of the Ϫ858c/t polymorphism and the two previously reported diabetes-associated polymorphisms (rs1884614 and Thr130Ile) (data not shown) (15,18).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…17,25,26 HNF4a is expressed in different tissues, and mutated proteins may have wide ranging effects. The HNF4a gene is highly conserved across species, with two activation function domains, AF-1 and AF-2, a DNA-binding domain and a putative ligand-binding domain.…”
Section: Discussionmentioning
confidence: 99%